1993
DOI: 10.1080/01140671.1993.9513776
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fertigation and hydrogen cyanamide on fruit production, nutrient uptake, and fruit quality in kiwifruit

Abstract: In a 3-year field trial, kiwifruit (Actinidia deliciosa) vines received 40% of their nutrient requirements by fertigation and the rest as solid fertiliser. All plots received 158 kg/ha nitrogen (N) and 294 kg/ha potassium (K). After 3 years the vines receiving fertigation showed no advantage over those receiving a conventional solid fertiliser programme in yield, or leaf nutrient levels for kiwifruit. The quality of fruit from vines supplied with or without fertigation was assessed at harvest, and at several t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Fertigation has therefore been associated with a large reduction in N losses from the soil in apples in a semiarid region of Canada where irrigation is required to maintain productivity (Neilsen and Neilsen, 2002). Early studies of fertigation in 'Hayward' kiwifruit production in New Zealand (Marsh and Stowell 1993) showed no beneficial effects on the yield or fruit quality, but the researchers did not investigate nutrient use efficiency. In apples, a comparison of broadcast and fertigation application has suggested that N application rates can be lowered by 75% using fertigation, but again, there were no effects on yield or fruit quality (Neilsen et al 1999).…”
Section: Adopting New Application Techniquesmentioning
confidence: 99%
“…Fertigation has therefore been associated with a large reduction in N losses from the soil in apples in a semiarid region of Canada where irrigation is required to maintain productivity (Neilsen and Neilsen, 2002). Early studies of fertigation in 'Hayward' kiwifruit production in New Zealand (Marsh and Stowell 1993) showed no beneficial effects on the yield or fruit quality, but the researchers did not investigate nutrient use efficiency. In apples, a comparison of broadcast and fertigation application has suggested that N application rates can be lowered by 75% using fertigation, but again, there were no effects on yield or fruit quality (Neilsen et al 1999).…”
Section: Adopting New Application Techniquesmentioning
confidence: 99%
“…acid washing to keep drip lines clean. A number of earlier New Zealand studies examined fertigation of crops using drip irrigation systems, and found that fertigation was of no benefit for kiwifruit on deep free‐draining soils . Other research found mixed benefits to fertigating onions and squash in a fertile sandy loam soil…”
Section: Precision Fertigation Of Nutrientsmentioning
confidence: 99%
“…A number of earlier New Zealand studies examined fertigation of crops using drip irrigation systems, and found that fertigation was of no benefit for kiwifruit on deep free-draining soils. 32,33 Other research found mixed benefits to fertigating onions and squash in a fertile sandy loam soil. 34 Sub-surface drip irrigation of pastures has been trialled in Australia, during a severe shortage of fresh water.…”
Section: Precision Fertigation Of Nutrientsmentioning
confidence: 99%